2022
DOI: 10.1155/2022/1231843
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation to Analyze the Mechanical and Microstructure Properties of 310 SS Performed by TIG Welding

Abstract: In present experimental work, 310 SS alloy has been welded by the TIG welding using design of experiment and grey relation optimization techniques. The input parameters, i.e., welding current, welding gas flow rate, and welding voltage, have been selected to perform the TIG welding. The same filler material was used during the welding process to investigate the mechanical and microstructure properties. The design of experiment and grey relation optimization techniques were used to optimize the effect on hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Goyal et al [12] considered 310 SS Alloy TIG welding through the Design of Experiment (DOE) application plus the grey relation optimization technique. They found that at 65 A welding current and 10 V voltage specimen achieved enhanced tensile strength while 75 A current and 10 V voltage achieved reduced tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Goyal et al [12] considered 310 SS Alloy TIG welding through the Design of Experiment (DOE) application plus the grey relation optimization technique. They found that at 65 A welding current and 10 V voltage specimen achieved enhanced tensile strength while 75 A current and 10 V voltage achieved reduced tensile strength.…”
Section: Introductionmentioning
confidence: 99%